A study of indoor thermal parameters for naturally ventilated occupied buildings in the warm-humid climate of southern India. (15th March 2019) - Doctor-Pingel, Mona; Vardhan, Vishnu; Manu, Sanyogita; Brager, Gail; Rawal, Rajan
Abstract: The ever-increasing demand for built spaces to cater to the needs of the tropical population compels for the adoption of sustainable building forms and passive design strategies. This research aims at studying the cases of six naturally ventilated occupied buildings constructed in the tropical 'warm and humid' climate of Pondicherry and Auroville, India. The buildings were subjected to long-term data logging and sporadic hand-held measurements. Indoor parameters of air temperature (Ta ), surface temperature (Ts ), and relative humidity (RH) across six living spaces, eight roof assemblies, and six passive design strategies were logged on an hourly basis and analysed for the hottest and coldest months. In order to estimate the thermal comfort, Ta readings of the most occupied zones were compared against ASHRAE-55 adaptive thermal comfort model and India Model for Adaptive Comfort (IMAC) temperature limits. This research showed that the hourly averaged Ta and RH in the six naturally ventilated spaces at the hottest summer hour (13:00) was between 31.0 and 33.2 °C and 56.0–69.0% while the outdoors were at 36.9 °C and 43.3% respectively. The hourly averaged rooftop and ceiling Ts for the unshaded roofs at 14:00 h during peak summer was between 53.0-43.4 °C and 36.6–31.0 °C respectively, while a shaded roof had a rooftop and ceiling Ts of 34.5 °C and 31.9 °C respectively. The passive design strategies of exposed cavity walls, night ventilation, and optimised building forms were found to be the most effective. The number of uncomfortable hours predicted by the ASHRAE model were found to be 93.4% higher than those by IMAC. Highlights: 51, 504 h of temperature and RH data across six buildings is recorded. Surface temperatures across eight roofing strategies are analysed. Temperatures across six passive design strategies are analysed. Adaptive thermal comfort is estimated as per ASHRAE-55 and IMAC standards.